Cost-affordable and qualified powder metallurgy metastable beta titanium alloy by designing short-process consolidation and processing. (15th February 2021) - Zhao, Qinyang; Chen, Yongnan; Xu, Yiku; Torrens, Rob; Bolzoni, Leandro; Yang, Fei
Abstract: Short-time processing route has been designed to manufacture cost-affordable and high-quality powder metallurgy (PM) metastable β titanium alloy, containing rapid powder consolidation (modified thermomechanical pressing), one-step thermomechanical processing (simple open die uniaxial hot forging by industrial press) and fast heat treatment (one-step annealing at various temperatures for only one hour). Based on comprehensive microstructure characterizations and mechanical property examinations, underlying microstructural evolution mechanism and microstructure-property relationship of the produced alloys were uncovered and elucidated thoroughly. Homogeneous macrostructure and fine-grain microstructure without undissolved particles and large pores are obtained for the alloy after thermomechanical powder consolidation as a result of the concurrent effect of external deformation and high-temperature diffusion. One-step open-die forging is verified to produce full-dense and sound PM alloy pancake with large-scale and high strength. Attributed to the harmonious concurrence of hierarchical α precipitation and heterogeneous grain structure, synergistic strength-ductility combinations are achieved for the alloy after specific processing and heat treatment with the tensile strength and strain at failure values of 1386.5 MPa/7.3% and 1252.3 MPa/9.0%, respectively. These strength-ductility combinations are comparable and/or even better than other metastable β titanium alloys prepared by some PM and ingot metallurgy approaches with relatively high cost and time consumption. Graphical abstract: Unlabelled Image Highlights: Short-time processing route is designed to produce cost-affordable and high-quality powder metallurgy titanium alloy. Rapid consolidation, one-step processing and fast heat treatment are applied to minimize the manufacturing cost and time. Superior strength-ductility combinations are achieved for the alloy after specific processing and fast heat treatment. The excellent mechanical properties are comparable to other expensive and time-consuming metastable β titanium alloys.